Case Report: Endoscopic submucosal dissection and endoscopic transcecal appendectomy for synchronous sigmoid and appendiceal adenomas with calcified Schistosoma eggs - Zhou, Yu; Zhu, Liying; Niu, Duoshan; Xu, Li; Xu, Xiaowu; Kang, Xingxing; Du, Yemei; He, Daoxing (Frontiers in Oncology, 2025)
BackgroundSchistosomiasis is an endemic parasitic disease still prevalent in some regions of China. Chronic infection may cause recurrent inflammation and intestinal mucosal remodeling, increasing the risk of lesions such as adenomas. Although intestinal lesions associated with schistosomiasis have been reported, cases involving both the colon and appendix with egg deposition are rare. With the maturation of natural orifice transluminal endoscopic surgery (NOTES), endoscopic transcecal appendectomy (ETA), a specific NOTES technique, has been increasingly applied in clinical practice. In this case, two lesions in the colon and appendix were completely resected using endoscopic submucosal dissection (ESD) followed by ETA, offering a novel approach for the minimally invasive treatment of complex lesions.Case presentationA 77-year-old woman presented with hematochezia. Colonoscopy revealed a bulging lesion in the sigmoid colon obstructing the passage of the scope. After complete resection of the lesion by ESD, the scope was advanced to the ileocecum, where a tumor-like lesion protruding from the appendiceal orifice was identified. ETA was subsequently performed with pathologic and imaging confirmation.ConclusionThis case suggests that Schistosoma haematobium infection may contribute to intestinal epithelial neoplasia. The combination of ESD and ETA offers a safe and feasible minimally invasive strategy for the treatment of concurrent colonic and appendiceal lesions.